2002
DOI: 10.1523/jneurosci.22-11-04550.2002
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 5-HT1B Receptor in Dorsal Raphe Nucleus Using Herpes Simplex Virus Gene Transfer Increases Anxiety Behavior after Inescapable Stress

Abstract: 5-HT(1B) autoreceptors have been implicated in animal models of stress and are regulated selectively by serotonin-selective reuptake inhibitors such as fluoxetine. These terminal autoreceptors regulate serotonin release from dorsal raphe nucleus (DRN) projections throughout rat forebrain. However, it has not been previously possible to manipulate 5-HT(1B) autoreceptor activity selectively without also changing 5-HT(1B) activity in other neurons mediating different behavioral responses. Therefore, we have devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 76 publications
4
105
0
Order By: Relevance
“…Previous work from this lab has demonstrated the potential uses of viral-mediated gene transfer to investigate the functions of other serotonin receptors in discrete brain regions (Clark et al, 2002(Clark et al, , 2004Neumaier et al, 2002;Hoplight et al, 2006). We confirmed that the HAtagged 5-HT 6 receptor functioned identically to wild-type receptor in vitro, and the anatomical pattern of distribution of the transgenic 5-HT 6 receptors appears to closely match the normal neuronal distribution of these receptors in striatum, albeit at higher levels.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Previous work from this lab has demonstrated the potential uses of viral-mediated gene transfer to investigate the functions of other serotonin receptors in discrete brain regions (Clark et al, 2002(Clark et al, , 2004Neumaier et al, 2002;Hoplight et al, 2006). We confirmed that the HAtagged 5-HT 6 receptor functioned identically to wild-type receptor in vitro, and the anatomical pattern of distribution of the transgenic 5-HT 6 receptors appears to closely match the normal neuronal distribution of these receptors in striatum, albeit at higher levels.…”
Section: Discussionsupporting
confidence: 77%
“…In order to visualize neurons expressing transgenes, the GFP protein was coexpressed along with HA-5-HT 6 receptor from the viral amplicon. GFP expression has been shown to be present throughout the cytosol in infected cells (Clark et al, 2002). To allow direct observation of transgenic 5-HT 6 expression, we 'tagged' the 5-HT 6 receptor with HA to identify 5-HT 6 -overexpressing cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations